2018
DOI: 10.1063/1.5054654
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hall current and wall conductivity on hydromagnetic mixed convective flow in a rotating Darcian channel

Abstract: In the present study, an analysis for steady hydromagnetic mixed convective generalised Couette flow between two infinite parallel plates of arbitrary electrical conductivities and finite thicknesses filled with a porous medium in the presence of a uniform transverse magnetic field in a rotating system with the Hall effect is presented. The heat transfer characteristics of the fluid flows are also investigated, taking viscous and Joule dissipations into account. Exact solutions of the resulting simultaneous or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 46 publications
0
50
0
Order By: Relevance
“…Thereafter, Nandkeolyar et al 38 investigated the steady mixed convective boundary layer flow over a vertical plate with an induced magnetic field under the action of an aligned magnetic field. Recently, Singh et al 39 extended the problem studied by Seth and Singh 36 and studied the effects of Darcian drag force on MHD mixed convection flow in a horizontal channel with arbitrarily conducting walls. In their investigation, they found that reverse flow is observed in the secondary flow direction when Darcian drag force is very large.…”
mentioning
confidence: 99%
“…Thereafter, Nandkeolyar et al 38 investigated the steady mixed convective boundary layer flow over a vertical plate with an induced magnetic field under the action of an aligned magnetic field. Recently, Singh et al 39 extended the problem studied by Seth and Singh 36 and studied the effects of Darcian drag force on MHD mixed convection flow in a horizontal channel with arbitrarily conducting walls. In their investigation, they found that reverse flow is observed in the secondary flow direction when Darcian drag force is very large.…”
mentioning
confidence: 99%
“…In similar situations, the Hall current must be included in the generalized ohm's law. The magnetic induction equation with Hall effect is expressed as (Seth and Singh [5], Singh et al [8,10]…”
Section: Fig 1 Flow Configuration Of the Physical Problemmentioning
confidence: 99%
“…The study of mixed convection becomes important when both the free and force convection occur simultaneously and both the convective forces are comparable in magnitude. Motivated from these facts, recently, Mishra and Singh [1], Rashidi et al [2], Sajid et al [3], Nejad et al [4], Seth and Singh [5], Reddy et al [6], Ahmad et al [7], Singh et al [8][9][10] and Opanuga et al [11] presented the MHD mixed convection flow problems. A comprehensive literature survey on MHD mixed convective buoyancy driven flows reports Science and Technology (2020), Volume 7,Issue 4,Paper No.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations